Cumulative Stress Burden and Cognitive Function in African American Adults Living in Low-Income Neighborhoods. (17th December 2021) - Fan, Erica; Dubowitz, Tamara; Troxel, Wendy; Weinstein, Andrea; Gary-Webb, Tiffany; Butters, Meryl; Ghosh-Dastidar, Bonnie; Rosso, Andrea
Abstract: African Americans (AA) are more likely to experience stressors due to racial discrimination and segregated neighborhoods, potentially contributing to higher risk for dementia. We investigated the association between stressors and cognitive function in older AA adults through cumulative stress burden (CSB) indices. Stressors and cognitive domains were measured in 253 participants >50 years, recruited from primarily AA neighborhoods in Pittsburgh, PA. CSB included perceived and psychological distress, unfair treatment, post-traumatic stress disorder, and neighborhood-level stressors such as walkability, safety, satisfaction, and social cohesion. Indices were formed by dichotomizing stressor scores and summing. Cognitive domains were z-scores adjusted for age, sex, and education. Adjusted generalized linear models assessed the relation between CSB indices and cognition, and between specific stressors and cognition. Interactions with age were tested. Greater individual-level CSB index was associated with lower language (□= -0.11, p= 0.03) and executive function (□= -0.087, p=0.04). The neighborhood-level CSB index was not associated with any cognitive domain. The combined index was marginally associated with language in adjusted models (□= -0.07, p= 0.05). There were no significant associations between specific stressors and cognition, except for neighborhood safety with 3MS (□= -0.28, p= 0.001) and language (□= -0.16, p= 0.02). Age interactions indicate that findings were stronger for younger participants. Greater cumulative stress is associated with poorer cognitive function in some domains in older AA. A comprehensive assessment of cumulative stress is vital in understanding the dimensionality of racialized stress for older adults potentially experiencing cognitive decline.